Urgency of Islamic Education in Constructing Noble Behavior: Family Structure as The Basis and Foundation of Micro-Scale Community Reform Commencement - Habrun Habrun (Didaktika Religia, 2017)
Islamic education in the family means education provided by members of the family, especially parents, to their children in the family environment to form the child's personality in order to be a muslim in which the attitude and behavior is in accordance with the teachings of Islam. The motivation of parent’s devotion in educating their children is solely for the sake of natural love, so, in this atmosphere of love, the process of education takes place well since the child is dependent to the family. Urgency of Islamic education in the family in building children’s noble character is the realization of the ideal human; intelligent and fear Allah SWT.